Pengaruh Angin Terhadap Tata Letak dan Jumlah Sekrup Konstruksi Baja Ringan Berdasarkan SNI-7971- 2013 - Syahbana, Mahdi; Agustiar, Agustiar; Lindawati, Lindawati (University of Muhammadiyah Aceh, 2021)
Light weight steel material has experienced rapid development in the construction. However, there are still many costruction failures on light weight steel, resulting in cost loss. The failure of light steel structures often occurs at the connections. The connection tool on milld steel is usually using a self-drilling screw. The research location is at Aceh One Stop Integrated Service and Investment Service Building (DPMPTSP) Aceh. The problem in this study is the placement and number of screws on the lightweight steel roof structure in the field which is carried out for each member according to the code, and the effect of wind load on the placement and number of screws on the lightweight steel roof structure. This study aims to determine the effect of the placement and number of screws on the lightweight steel roof structure. The scope of this research of problems including the placement and number of screws on the lightweight steel roof structure. The standars used in the design of light steel structures in this study is SNI 7971 2013 and the loading planning standars using SNI 03 1727 1989. Calculation steps using the LRFD method for steel structure design regulated in SNI 03 1729 2002. Based on the results, it is obtained that the number and placement of the screws in the field are different from those obtained in the calculation. From the calculations, it is obtained from the recapitulation, dead loads with a maximum value of 123.07 kg, live loads with a maximum load of 30.1 6 kg, and for compressed air and suction loads with a maximum load of 180 kg. the maximum design force value is 1241.33 kg and the screws bearing resistance value is 256.752 kg. the number of screws is obtained where the the value of the design force is divided by the value of the bearing resistance, on each member obtained 1screw, 2 screws, 3 screws, 4 screws, and 5 screws. Whilst it is found for each member in the field using 3 screws.